Climate signals in stable carbon and hydrogen isotopes of lignin methoxy groups from southern German beech trees - Wieland, Anna; Greule, Markus; Roemer, Philipp; Esper, Jan; Keppler, Frank (Climate of the past discussions, 2021)
Stable hydrogen and carbon isotope ratios of wood lignin methoxy groups (δ13CLM and δ2HLM values) have been shown to be reliable proxies of past temperature variations. Previous studies showed that δ2HLM values even work in temperate environments where classical tree-ring width and maximum latewood density measurements are less skilful. Here, we analyse annually resolved δ13CLM values from 1916-2015 of four beech trees (Fagus sylvatica) from a temperate site near 15 Hohenpeißenberg in southern Germany and compare these data with regional to continental scale climate observations. Initial δ13CLM values were corrected for the Suess effect (a decrease of δ13C in atmospheric CO2) and physiological tree responses to increasing atmospheric CO2 concentrations considering a range of published discrimination factors. The calibration of δ13CLM chronologies against instrumental data reveals highest correlations with regional summer (r = 0.68) and mean annual temperatures (r = 0.66), as well as previous-year September to current-year August temperatures (r = 0.61), all calculated from 20 1916-2015 and reaching p < 0.001. Additional calibration trials using detrended δ13CLM values and climate data, to constrain effects of autocorrelation on significance levels, returned rsummer = 0.46 (p < 0.001), rannual = 0.25 (p < 0.05) and rprev.Sep-Aug = 0.18 (p > 0.05). The new δ13CLM chronologies were finally compared with previously produced δ2HLM values of the same trees to evaluate the additional gain of assessing past climate variability using a dual-isotope approach. Compared to δ13CLM, δ2HLM values correlates substantially stronger with large-scale temperatures averaged over western Europe (rprev.Sep-Aug = 0.69), 25 whereas only weak and mainly insignificant correlations are obtained between precipitation and both isotope chronologies (δ13CLM and δ2HLM values). Our results indicate great potential of using δ13CLM values from temperate environments as a proxy for local temperatures, and in combination with δ2HLM values, to assess regional to sub-continental scale temperature patterns.
Gesehen am 27.10.2022